Pengaruh Penyuluhan Kesehatan Terhadap Tingkat Pengetahuan (Tahu) Remaja Mengenai Sleep Hygiene (Penelitian di SMA Katolik Stella Maris Surabaya ) - Suhariyanto, Yosi Slamet; Widianingtyas, Sisilia Indriasari; Prastyawati, Irine Yunila (JURNAL NERS LENTERA, 2024)
Sleep hygiene refers to behaviors that can effectively improve the quality of sleep. At SMAK Stella Maris Surabaya, many students experience sleep disturbances at night. This study aimed to analyze the impact of health education on the level of knowledge about sleep hygiene among adolescents at SMAK Stella Maris Surabaya. This research employed a pre-experimental design with a OneGroup Pre-Post Test Design, with the research variable being the level of knowledge. The study population consisted of 11th-grade students, with a sample size of 56 respondents selected through simple random sampling. Data was collected using a questionnaire that assessed the level of knowledge about sleep hygiene. The results showed that before the health education, more than 50% (79%) of the respondents had a low level of knowledge. However, after the health education, it was found that 100% of the respondents had a good level of expertise. The Wilcoxon test showed a p-value of 0.000 with a Z score of 6.798, indicating that p < α. With the post-test results showing a significant improvement, health education positively impacted the adolescents’ knowledge level regarding sleep hygiene. It is recommended that the school provides health education to students who have not yet received information about sleep hygiene. Keywords: health education, knowledge, Sleep Hygiene